Floral biology, flowering behaviour and fruit set development of Jatropha curcas L. in Malaysia - Noor Alam, Noor Camellia; Abdullah, Thohirah Lee; Abdullah, Nur Ashikin Psyquay (Universiti Putra Malaysia Press, 2012)
This paper describes the flowering behaviour of Jatropha curcas cultivated under Malaysian tropical climate. Investigation was carried out by observing the floral morphology, flowering sequence of pistillates, floral anthesis time, flower daily anthesis, flowering and fruiting plant behaviour, flower sex and fruit set ratio. Floral reproductive organs were examined using Scanning Electron Microscope (SEM). Jatropha is monoecious and it produces individual flowers in a dichasial cyme. Each Jatropha inflorescence has at least six compound cymes. The male flower anthesis started the earliest at 12.00 am and once again at 6.10 am to 6.46 am. The female flower anthesis commenced at 6.35 am to 8.25 am. The male flowers opened for a period of 8 to 11 days, while the female flowers opened for only 3 to 4 days. The reading of the male to the female flower ratio was taken twice, 22:1 in December 2008 and 27:1 in April 2009. The flower to fruit ratios were 6:5 (January 2009) and 2:1 (May 2009). Numerically, 0-10 female flowers and 25-215 male flowers are produced in the same inflorescence. In this study, the terminal stem of Jatropha bore fruits profusely in January, May and August 2009. Meanwhile, the development of the floral meristem consists of three stages which include a vegetative stage, a transition from vegetative to floral stage and development of flower parts. The meristem was in the transition stage at day 6. Although all sepals and a petal were developed at day 18, the presence of reproductive organs developing at this particular stage was not detected. Flower and fruit development took approximately 3 months to complete the full cycle, i.e. from the initiated floral bud stage until fruit maturity.